The Role Of Fear Of Missing Out (Fomo) In Mediating The Effect Of Scarcity Perception On Impulse Buying - Putu Ayu Trisna Febrianty; Ni Putu Dera Yanthi; I Gst. Ayu P. Jesika Sita Devi N; Ni Made Intan Kusumasari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The digital age has introduced a new paradigm where global connectivity and instant information access are integral to everyday life. Advancements in digital technology have reshaped various aspects of human activities, including communication, work, education, and shopping. This study explores how consumers' fear of missing out (FOMO) functions as an intermediary in the interaction between perceived scarcity and impulsive purchasing behavior. The study involved 200 respondents, who were e-commerce consumers of Shopee in Denpasar. Purposive sampling was used in data collection through questionnaires. The analysis was carried out using SEM PLS 3.0. The test results reveal that scarcity perception does not have a significant influence on impulse buying. However, FOMO has a notable effect on impulse buying and serves as a mediator in the relationship between scarcity perception and impulse buying. This study is expected to enrich the literature and provide practical insights for companies in formulating marketing strategies.